Severe Hepatotoxicity in Mushroom Poisoning by Lepiota brunneoincarnata from Complete Recovery to Liver Transplantation: A Case Series with Review on Liver Function Tests and Liver Histopathology - Mohammad Hossein Anbardar; Neda Soleimani; Kourosh Kazemi; Zahra Jafarpour; Mahsa Hasani; Sahand Mohammadzadeh; Parnia Torfehnezhad; Sedighe Jafarian; Mahsa Farhadi; Mina Salari Sardari (International Journal of Hepatology)
Background. In spite of the scientific evidence supporting health advantages of mushrooms, some of them are seriously poisonous. The clinical picture of mushroom intoxication ranges from minor gastrointestinal symptoms to organ failure, such as liver failure and death. Method. We provided demographics, clinicopathological characteristics, applied treatments, and outcomes of mushroom poisoning by Lepiota species in a series of 18 cases that were referred from Kermanshah and Lorestan provinces to Abu-Ali-Sina Hospital, Shiraz, Iran. Clinical and paraclinical data were collected by taking history and reviewing of medical documents. Pathologic findings were extracted through a review of hematoxylin and eosin pathologic slides. Results. The patients were between the ages of 18 and 67 years, composed of ten females and eight males. The most frequent clinical manifestations were nausea and vomiting followed by abdominal pain. Four cases presented decreased consciousness on admission. One of them passed away. Three other cases underwent liver transplantation, two of them died after transplantation, and one fully recovered without any major issues. All instances had elevated ALT levels, which ranged from 44 to 9,140 IU/L (mean: 3259±2476), with most of them also having concurrent AST elevations (mean: 1,361±1,532). Only few patients had modest elevations in alkaline phosphatase. Total and direct bilirubin elevations up to 47.6 and 24 mg/dL, respectively, were found in most cases. Decreased total protein and albumin concentrations and increased BUN and creatinine levels were observed in some patients. In addition, some instances revealed increased LDH, increased WBC, decreased hemoglobin, and decreased platelet count. Most patients had increased prothrombin time; hematuria and positive stool occult blood were observed in few patients. Histopathologic examination of three explanted livers revealed massive necrosis with moderate to severe macrovesicular steatosis, significant ductular reaction, and parenchymal inflammation. Other patients followed a recovery process with a considerable drop in liver enzymes, especially ALT, during hospitalization utilizing conservative treatment. They had no liver problems or relevant issues after a two-year follow-up. Conclusion. In our study, highly elevated liver enzymes with a significantly high ALT/AST ratio were observed in cases of mushroom poisoning by Lepiota species, leading to fulminant liver failure and death in some cases. These laboratory findings were correlated with liver necrosis and macrovesicular steatosis in explanted livers.